EFEKTIVITAS LKPD INTERAKTIF BERBANTUAN PERMAINAN ULAR TANGGA DALAM MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN INFORMATIKA - Lusiana Putri, Vemi; Mutiara Felicita Amsal; Abna Hidayati; Fitri Maiziani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effectiveness of an interactive Student Worksheet (LKPD) assisted by a snakes and ladders game in increasing students' learning interest in Informatics learning for Grade VII students at MTsS TI. This study employed a Research and Development (R&D) approach using the 4D development model consisting of Define, Design, Develop, and Disseminate stages. The effectiveness test involved 29 Grade VII students. The instrument used to measure students' learning interest was a questionnaire administered before and after the use of the developed product. The data were analyzed using the Normalized Gain (N-Gain) score to determine the level of increase in students' learning interest. The results showed that the N-Gain scores obtained by the 29 students ranged from 0.76 to 1.00, and all students were included in the high category. The average N-Gain score was 0.96, equivalent to 95.79%, which was included in the effective category according to the effectiveness criteria used in the study. The results indicate that the interactive LKPD assisted by the snakes and ladders game is effective in increasing students' learning interest in Informatics learning.